Perancangan Tipikal Jembatan Menggunakan Metode Building Information Modeling - Agus Sutiono; Veronika Happy Puspasari (Jurnal Basement : Jurnal Teknik Sipil, 2024)
The development of technology is currently a challenge in the construction field. Building Information Modeling (BIM) is an example of technological advances in the construction field that help projects to be completed effectively and efficiently. Project planning for flood control works on the Sanggai River in Bumi Harapan Village was carried out to prevent flooding. Bumi Harapan Village, located in Sepaku Sub-district, Penajam Paser Utara District, East Kalimantan, is the planned capital city of the "Archipelago" (IKN). The BIM method can be used for simple construction work, such as typical bridge construction, and is not limited to building construction. The purpose of this paper is to design a 3D standard bridge model using the Building Information Modeling method, which will be carried out using the Autodesk Revit program. The results of BIM modeling include the 3D material created and the detailed information in it.